Cooperative Learning for Undergraduate Translation and Interpreting Classes - Yuliasri, Issy (Universitas Muhammadiyah Semarang, 2017)
Cooperative learning has been widely applied and studied in the field of English Language Teaching (ELT) and its advantages have been acknowledged, both in school contexts and in tertiary education. Although some scholars believe in the distinction between cooperative learning and collaborative learning, and that collaborative learning is more suitable for tertiary education, some others also believe that the terms are actually interchangeable. Despite the different ideas of the distinction and interchangeability of the two terms, there are evidences of the use of cooperative learning in tertiary education. Among the studies on the use of cooperative learning in higher education are those on the application of cooperative learning in the teaching of translation and interpreting. This paper discusses how cooperative learning is used and studied in the context of translation and interpreting classes in undergraduate program.